The Influence of Motivation, Attitudes and Obstacles for Middle School Students’ Participation in Leisure Activities on Their Leisure Satisfaction in Southwest China - Yunlan Wu; Jianan Sun; Falu Fan; Xia Wang; Yuanqiu Peng (Frontiers in Psychology, 2021)
Purpose: To explore the relationship among leisure motivation, barriers, attitude and satisfaction of middle school students in Chengdu, Sichuan, to help students establish a positive leisure attitude and provide a reference for youth leisure counseling.Methods: Based on consulting research literature, this paper designs a survey volume of teenagers’ leisure motivation, barriers, attitude, and satisfaction; 2249 valid questionnaires of middle school students in Chengdu were obtained by stratified random sampling. The data were statistically processed by the combination of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA).Results: (1) There are significant positive correlation effects between leisure motivation and leisure attitude, leisure attitude and leisure satisfaction, and leisure motivation and leisure satisfaction; (2) There is a low degree of positive correlation effect (r = 0.35 *) between leisure barriers and leisure motivation, which is contrary to common sense and needs to be further studied in the follow-up; (3) Leisure barriers has no significant direct impact on leisure satisfaction, but it can have a significant negative impact on leisure satisfaction with the intermediary variable of leisure attitude; (4) Leisure motivation is the most important variable in the whole leisure model structure. It not only has the greatest direct impact on leisure satisfaction but also has a great positive impact on leisure satisfaction through the intermediary of leisure attitude.Conclusion: Adolescent leisure motivation, barriers, attitude, and satisfaction are complementary and interdependent. Among them, leisure motivation is the core variable and leisure attitude is the dual intermediary variable. Through the initiation of leisure motivation, helping adolescents establish a positive leisure attitude may be the key to ensure their leisure satisfaction.